Standardization of extract of Leucaena leucocephala (lmk) De Wit seeds by α-glucosidase inhibitor - Syamsudin (International Journal of Phytomedicine, 2010)
Extracts of Leucaena leucocephala (lmk) De Wit seeds were collected from different areas in Java; they include Jakarta, Cengkareng, Bogor and Bandung. Each extract was examined for water content, ash content, acid-insoluble ash content, and α- glycosidase inhibition assay. The results showed that ethanolic extracts of Leucaena leucocephala (lmk) De Wit seeds collected from Bandung were found to be most active in inhibiting the formation of α-glycosidase compounds with an IC50 value of 7,46 ± 0,21 μg/ml, which was confirmed with ash content of 5,58 ± 0,04, acid-insoluble ash content of 0,55 ± 1,33, and water content of 26,22 ± 0,90.